Studi Antiviral Andrographis Paniculata, For Herpes Simplex Virustipe 1 (HSV-1) Treatment: In Slico Study - Mustarichie, Resmi; Megantara, Sandra (Asian Journal of Pharmaceutical Research and Development, 2021)
Herpes simplex virus type 1 (HSV-1) is a lifelong infectious disease. Research and drug development for this disease continues to be developed. Andrographis paniculata or commonly known as Sambiloto is a plant that is commonly used empirically as an HSV-1 drug. Further research is needed to determine the effectiveness of these plants as candidates for HSV-1 treatment. This study will determine several bioactive compounds contained in Sambiloto against the HSV-1 receptor in an insilico study which can be the basis for the discovery of new drugs in the treatment of HSV-1 infection.